Interactions at the molecular level between biphosphine ruthenium complexes and stearic acid in Langmuir and Langmuir-Blodgett films - Ferreira, Marystela; Wohnrath, Karen; Riul Jr., Antonio; Giacometti, José A. [UNESP]; Oliveira Jr., Osvaldo N. (American Chemical Society (ACS), 2002)
A molecular-level interaction between biphosphine ruthenium complexes and stearic acid has been observed in Langmuir and Langmuir-Blodgett (LB) films. Similar results were obtained for the ruthenium complexes mer-[RuCl3(dppb)(4-Mepy)] (dppb = PPh2(CH2)4PPh2; 4-Mepy = 4-methylpyridine) (Rupic) and mer-[RuCl3(dppb)(py)], (pyridine) (Rupy), which differ by the substituent group in the pyridine ring. The interaction was manifested in the Langmuir films by a nonlinear increase in the area per molecule and in surface potential with the relative concentration of the ruthenium complex in the mixture. In the LB films, interaction with stearic acid occurred via complexation with Rupy or Rupic, even though the latter are not charged. It is suggested that one of the chlorides is labilized, thus promoting complexation and keeping the Ru(III) oxidation state for the complex. Complexation was confirmed through FTIR data. Interaction with stearic acid enhanced the color change characteristic of biphosphine ruthenium complexes, which may be associated with an order-induced effect or with the exposure to the water subphase in the LB film preparation. In addition, X-ray diffraction experiments failed to detect separate domains of cadmium stearate, which is also attributed to the molecular-level interaction that prevents separate stearic acid or cadmium stearate domains from being formed.